Detection of growth sites in and protomer pools for the sheath of Methanospirillum hungatei GP1 by use of constituent organosulfur and immunogold labeling. - Southam, G (1992)
Methanospirillum hungatei GP1 integrated approximately 9% of cellular [35S]cysteine into its sheath. Autoradiography of sodium dodecyl sulfate-polyacrylamide gels revealed that [35S]cysteine was confined to the proteins released by the sodium dodecyl sulfate-beta-mercaptoethanol-EDTA solubilization method (G. Southam and T. J. Beveridge, J. Bacteriol. 173:6213-6222, 1991) and was not present in the proteins released by treatment with phenol (G. Southam and T. J. Beveridge, J. Bacteriol. 174:935-946, 1992). Limited labeling of exposed sulfhydryl groups on hoops produced from sheath material suggested that most organosulfur groups occur within hoops and therefore help contribute to resilience. Electron microscopic autoradiography demonstrated that sheath growth, which is most active at the sites of cell division (spacer region), occurs through the de novo development of hoops. For growth to occur in the spacer region, sheath precursors must transverse several periodic envelope layers, including the cell wall (a single layer) and the various lamellae of the spacer plug (T. J. Beveridge, G. D. Sprott, and P. Whippey, J. Bacteriol. 173:130-140, 1991).